2020
DOI: 10.1186/s12889-020-8358-9
|View full text |Cite
|
Sign up to set email alerts
|

Distorted body weight perception and its gender differences in middle-aged adults: population based study

Abstract: Background: Increasing interest in appearance and the growing preference for a beautiful body can lead to physical and psychological problems due to an inappropriate body image perception. As such, there is a need to identify what factors may contribute to an inappropriate body image. The purpose of this study was to examine the presence of distorted body weight perception among middle-aged Koreans and identify gender differences and other factors that contribute to a distorted body image regarding body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
2
8
0
3
Order By: Relevance
“…The young men in this study showed approximately eightfold higher misperceptions of their weight and a twofold higher lack of weight control effort compared to those in young women with obesity in Korea. Previous studies have reported similar findings [ 19 , 20 , 21 ]. A nationwide study of overweight and obese adults in the USA showed that 65.6% and 84.0% of men and women had accurate weight perceptions, and that 43.3% and 58.3%, respectively, had attempted to lose weight [ 19 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The young men in this study showed approximately eightfold higher misperceptions of their weight and a twofold higher lack of weight control effort compared to those in young women with obesity in Korea. Previous studies have reported similar findings [ 19 , 20 , 21 ]. A nationwide study of overweight and obese adults in the USA showed that 65.6% and 84.0% of men and women had accurate weight perceptions, and that 43.3% and 58.3%, respectively, had attempted to lose weight [ 19 ].…”
Section: Discussionsupporting
confidence: 85%
“…In the same context, gender differences in self-perceived weight status and weight control efforts have also been reported. In general, men were less likely to have accurate weight perception and to attempt weight loss compared to women [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over/underestimated indicates those with one stage of discrepancy between the perceived BMI category and actual BMI range. For example, “highly overestimated” accounted for those who responded as being “obese” on their weight status although their actual BMI was “normal.” Further, “overestimated” accounted for those who responded as being “overweight” while their actual BMI was “normal.” People in the “highly underestimated” category are those who responded as being “normal” even though their actual BMI was “obese.” Also, “underestimated” presents those who responded as being “normal” while their actual BMI was “overweight.” This assessment has been validated in previous studies ( Song et al, 2020 ). These five categories were rearranged into three categories accordingly: underestimation (combining highly underestimated and underestimated), appropriate estimation (BWP corresponded with their actual BMI), and overestimation (combining overestimated and highly overestimated) for analyzing their association with obesity-related psychological factors.…”
Section: Methodsmentioning
confidence: 82%
“… 2 , 22 , 23 Distorted perception of body image were found to be more prevalent among middle-aged men. 24 Among men, distorted body weight perception was found to be correlated with age (middle-age), income, perceived health status and health behaviors. In contrast to men, women who have distorted body weight perception were mostly psychological in nature.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to men, women who have distorted body weight perception were mostly psychological in nature. 24 Studies have shown the relationship between perceived weight and the intention to lose weight, and may be different across gender with women more likely to attempt weight loss than men. 25 , 26 A study showed that men were more likely to attempt weight loss, exercise more, eat less fat compared to women who prefer to take prescription pills and follow specific diets for weight loss.…”
Section: Introductionmentioning
confidence: 99%